Dye-Surfactant Solution of Coomassie Brilliant Blue G250 and Tween 20: Micellar and Interaction Parametric Studies. Issue 3 (May 2019) - Wang, Zhaoran; Jing, Jilei; Wang, Dailian; Tong, Junfeng; Wang, Nong
Coomassie brilliant blue G250 (CBBG250) is used in textile, printing, and biotechnology applications. Fluorescence probe, UV-Vis spectrophotometric, and electrical conductivity methods were used to study the interactions between CBBG250 and the surfactant Tween 20 in aqueous solution. The fluorescence intensity ratio of pyrene ( I 3 / I 1 ) in the mixed system showed that I 3 / I 1 increased significantly when the concentration of Tween 20 was greater than the critical micelle concentration ( cmc, 5.25 x 10 −5 mol/L ). The micropolarity of the association system decreased as the concentration of CBBG250 in the solution increased. All results show that an interaction between CBBG250 and Tween 20 existed. Thermodynamic parameters were then determined, showing that the association was a spontaneous process that was driven by both enthalpy and entropy.